Affective domain and mathematics achievement of Colombian students under multiple correspondence analysis - Prada Núñez, Raúl; Rabelo Procopio, Marcos V.; Fernández-Cézar, Raquel; Solano-Pinto, Natalia (Frontiers in Education, 2024)
The literature review indicates that age is a variable related to the students' affects towards mathematics, in such a way that the older they are, the less affection they feel for mathematics. In the case of the Department of Norte de Santander, the administration is going to carry out an educational programme for 2050 whose aim is to make this region a STEAM territory, for which it is necessary for students, regardless the grade, to reach optimum levels in the management of mathematical competences. Therefore, to have a picture of the department situation in this respect is relevant. To this end, this research aims to apply a quantitative and descriptive methodology on the affective domain and achievement in mathematics, to determine whether these vary with the students' grade level. A non-probabilistic sample of 2729 students from fourth to eleventh grades (9 to 18 years old) from thirteen educational institutions in a region of north-western Colombia was used. The instrument used characterised the affective domain towards mathematics (attitudes, beliefs, and emotions) and math achievement, taking grade as the independent variable. A multiple correspondence analysis was carried out to depict the affective domain towards mathematics in relation to grade level, considering also as factors whether students like the subject and achievement. The results allow to identify that for beliefs and attitudes, the favourable values are located towards the positive axis of the abscissae, contrary to what is found for emotions. It is noteworthy that students in the lowest grade, fourth grade, show positive beliefs, attitudes, and emotions towards mathematics as well as high achievement, while those in the last grade, eleventh grade, show low values of the three components, besides low performance. This situation is worrying since mathematical knowledge is immersed in everyday life and is necessary for citizens in the development of any profession. For this reason, it should be considered by the concerned administration when developing the STEAM programme in order to promote an improvement in mathematical performance by accompanying students in the development of their affects towards mathematics.